Liminal roles as a source of creative agency in management: The case of knowledge-sharing communities. (March 2016) - Swan, Jacky; Scarbrough, Harry; Ziebro, Monique
Studies suggest that the experience of liminality – of being in an ambiguous, 'betwixt and between' position – has creative potential for organizations. We contribute to theory on the link between liminality and creative agency through a study of the coordinators of 'knowledge-sharing communities'; one of the latest examples of a 'neo-bureaucratic' practice that seeks to elicit innovative responses from employees while intensifying control by the organization. Through a role-centred perspective, our study found that both the structural and interpretive aspects of coordinators' role enactments promoted a degree of creative agency. 'Front-stage' and 'back-stage' activities were developed to meet the divergent expectations posed by senior management and community members, and the ambiguity of their roles prompted an array of different role interpretations. Our findings contribute to theory by showing how the link between liminality and creative agency is not confined to roles and spaces (consultancy work, professional expertise) that are positioned across organizational boundaries, or free from norms and expectations, but may also apply to roles that are ambiguously situated within organizational contexts and that are subject to divergent expectations. This shows how neo-bureaucratic forms may be both reproduced and renewed through the creative responses of individual managers.